ผลของยาฟีโนไฟเบรตในขนาดต่าง ๆ ต่อระดับกรดยูริกในเลือดและในปัสสาวะในผู้ป่วยโรคเกาต์ที่ยังมีระดับกรดยูริกในเลือดสูงหลังจากได้รับยาลดกรดยูริกที่เป็นมาตรฐานแล้ว - อธิพงศ์ สูริประเสริฐ (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
Evaluates the effects on serum uric acid of 2 different dosages of fenofibrate in patients with gout and hyperuricemia after receiving standard urate-lowering agents. Twenty-six patients with gout were enrolled in this randomized, double-blind, placebo-controlled trial and were allocated to receive 300mg of fenofibrate daily (11 patients), 100mg of fenofibrate daily (11) or placebo (11) for 8 weeks. All patients had a stable dose of urate-lowering agents (allopurinol or benzbromarone) for at least 3 months before participating the study. No modification of the dose of urate-lowering agents or additional drugs was allowed throughout the study. The primary outcome of this study was the differences in serum uric acid at baseline and 8 weeks of treatment among the 3 groups. Results: The mean+-SD age of the patients was 58.3+-14.5 years, and 78.8% were men. Thrity-two patients (97%) were taking allopurinol at mean+-SD dose of 121.1+-53.1 mg. Serum uric acid levels were lowered by 1.6+1.5 mg/dl (20.9+-16.6%) in 300-mg fenofibrate group and 0.9+-0.8 mg/dl (11.6+-9.4%) in 100-mg fenofibrate group after 8 weeks of treatment, which were significantly better than placebo group. Urine urate excretion was increased significantly after treatment with 300 mg of fenofibrate daily (p=0.002), but in 100-mg fenofibrate and placebo group, no such effect was found. No significant difference in the serious adverse events was found among the 3 groups. Conclusion: Fenofibrate, either 100-or 300-mg daily may be used as an effective add-on urate-lowering therapy in patients with gout, especially in those with coexisting hypertriglyceridemia.